Sustainable synthesis of silver nanoparticles using fruit waste and its antibacterial activity. (2022) - Rajput, Hitesh; Kedia, Abhitosh; Shah, Dimple; Gamit, Harshida A.; Amaresan, Natrajan
Abstract: Herein we have employed efficient, inexpensive and eco-friendly green synthesis process to produce well-defined geometries of silver nanoparticles at room temperature by utilizing fruit extracts (Punica granatum and Artocarpus heterophyllus) having unique optical, antibacterial and catalytic property. Reducing or anti-oxidant properties of phytochemicals present in fruit waste are typically responsible for reduction of metal precursor into their respective nanoparticles. Occurrence of surface plasmon resonance (SPR) peak in visible region (around 420 nm) as characterized by UV–Vis spectroscopy indicates formation of silver nanoparticles further confirmed via Transmission electron microscopy (TEM) measurements. The average size and stability are detected by dynamic light scattering (DLS), zeta potential analysis and TEM measurements. Crystallinity and face-centered cubic (fcc) structure of formed silver nanoparticles are examined via selected electron area diffraction (SEAD) pattern. Antibacterial sensitivity of formed silver nanoparticles against the bacteria E Coli is also determined.